CMV Serovirulance in Mothers and Their Very Low Birth Weight ( - Mohammad Kazemian; Mahsa Mehri; Minoo Fallahi; Maryam Khoshnud Shariati; Mahmoud hajipour; Ali Nikkhah (Mashhad University of Medical Sciences, 2022)
Background: Cytomegalovirus (CMV) is a pathogenic virus that is found everywhere. The serovirulance of this virus varies widely among different communities. The present study was conducted to investigate the frequency of CMV serovirulance in mothers and their very low birth weight (<1,500 g) neonates. Methods: This descriptive cross-sectional study was conducted on 234 serum samples (117 maternal and 117 neonatal samples) for 12 months in Mahdieh Hospital, Tehran, Iran, from March 2019 to March 2020. The enzyme-linked Immunosorbent assay technique was used to evaluate specific antibodies (i.e., immunoglobulin G [IgG] and immunoglobulin M [IgM]) of CMV. Statistical analysis was conducted in SPSS (version 23). Results: Based on the results, the seroprevalence of CMV IgG was 98.2% (115 cases) in mothers and 84.6% (99 cases) in neonates. The seropositivity rate of CMV IgM was reported at 1.8% (2 cases) in mothers and 0.9% (1 case) in neonates. It was found that the relationship between the mean scores of maternal CMV IgG and the number of live births was statistically significant (P=0.002). However, there was no statistically significant relationship between some maternal factors (e.g., age, occupation, living place, number of pregnancies, deliveries, abortions, and education) and maternal CMV IgM seropositivity. Furthermore, neonatal gender and gestational age showed no statistically significant relationship with maternal and neonatal CMV IgG and IgM seropositivity. Conclusion: According to our findings, the serovirulance of CMV in mothers and their neonates was significant, whereas active CMV infection in both groups was highly unusual. Additionally, the transmission rate of CMV IgG and CMV IgM from the mother to her neonate was incomplete.